Medicinal and Environmental Indicator Species of Utricularia from Montane Forest of Peninsular Malaysia. (30th April 2012) - Haron, Noorma Wati; Chew, Ming Yee
Abstract : The carnivorous Utricularia (Lentibulariaceae) is a small herb of multifarious wet habitats worldwide. Eleven of the 14 Peninsular Malaysian species range into the mountains. Distribution, disturbance adaptability and collection frequency were used to formulate their commonness category. Common ( U. aurea, U. bifida, and U. minutissima ) and fairly common ( U. gibba and U. uliginosa ) species are mostly lowland plants that ascend to open montane microhabitats, while the fairly common ( U. striatula ), narrow-range ( U. caerulea pink form and U. involvens ), rare ( U. furcellata and U. scandens ), and endemic ( U. vitellina ) species are restricted to mountainous sites. Common species that colonise dystrophic to oligotrophic man-made sites in late succession could serve as predictors for general health and recovery of wet habitats. Rarer species are often locally abundant, their niches situated around pristine forest edges. When in decline, they indicate the beginning of problems affecting the forest. Utricularia is reportedly nutritious, mildly astringent, and diuretic. Preadapted to nutrient-poor, waterlogged soils, U. bifida is suitable as an alternative for small-scale herb cultivation on low pH, wet poor soils usually deemed not suitable for any crops.